Sociological Criticism on Song Lyrics This Is Me by Keala Seattle - Sakilla Kurnia; Putu Lirishati Soethama; Ni Luh Ketut Mas Indrawati; Yana Qomariana (Program Studi Pendidikan Bahasa Inggris, STKIP Kie Raha Ternate, 2023)
Social issues such as racism, gender inequality, and social class differences are commonly found in today’s society. There are a bunch of literary works that carried a discussion of various social issues in various forms of literature. One of them is a movie entitled The Greatest Showman which showed the struggles of being different in the context of appearance and background. The data of this study was taken from one of the movie’s original soundtracks, This Is Me, by Keala Seattle. This study was a descriptive qualitative study that analyzed the data through words and sentences. This study was aimed at (1) showing which lyrics of the song This Is Me by Keala Seattle represented the struggle of her people, (2) describing how society saw people who were born differently in the movie The Greatest Showman represented in the song lyrics This Is Me by Keala Seattle, and (3) describing how people who were born differently faced society in the movie The Greatest Showman represented in the song lyrics This Is Me by Keala Seattle. The results showed that the characters faced numerous social issues as individuals due to their appearance and identity. In the end, the character gained strength and finally was able to accept themselves.